Migration, remittances, poverty, and human capital : conceptual and empirical challenges - Sasin, Marcin J. (The World Bank, 2007)
This paper reviews common challenges faced by researchers interested in measuring the impact of migration and remittances on income, poverty, inequality, and human capital (or, in general, "welfare") as well as difficulties confronting development practitioners in converting this research into policy advice. On the analytical side, the paper discusses the proper formulation of a research question, the choice of the analytical tools, as well as the interpretation of the results in the presence of pervasive endogeneity in all decisions surrounding migration. Particular attention is given to the use of instrumental variables in migration research. On the policy side, the paper argues that the private nature of migration and remittances implies a need to carefully spell out the rationale for interventions. It also notices the lack of good migration data and proper evaluations of migration-related government policies. The paper focuses mainly on microeconomic evidence about international migration, but much of the discussion extends to other settings as well